Birds observed during the monitoring period of 2013-2017 in the revegetation area of ex-coal mining sites in South Kalimantan, Indonesia - MOCHAMAD ARIEF SOENDJOTO; MAULANA KHALID RIEFANI; DIDIK TRIWIBOWO; DEWI METASARI (Society for Indonesian Biodiversity, 2018)
Soendjoto MA, Riefani MK, Triwibowo D, Metasari D. 2018. Birds observed during the monitoring period of 2013-2017 in the revegetation area of ex-coal mining sites in South Kalimantan, Indonesia. Biodiversitas 19: 323-329. The number of bird species in the reclaimed and revegetated ex-mine site increases as the vegetation age increases. To test the hypotheses, the number of bird species was recorded at 08.00-12.00 and 14.00-17.00, 6-8 days for eight consecutive semiannual monitorings of 2013-2017 in four revegetation sites. Since the second half of 2015, another revegetation site, namely BP was added. Bird species were recorded in 25 m right side and 25 m left side of the observation path and within a radius of 25 m of observation points. To show an increase in the number of bird species, the number of newly discovered bird species in the given semiannual monitoring was added to the number of bird species in the previous semiannual monitoring. The number of bird species in the early semiannual monitoring was used as the baseline value. A bird species was categorized as a resident if the species was observed in each monitoring in the four vegetated sites. Up to the last monitoring, 53 bird species were recorded in the first four sites and 70 bird species in five sites (four reclamation and revegetation sites and one additional site, BP), while in the early semiannual monitoring (second half of 2013) birds recorded were only 30 species. This result shows that the older the vegetation age in the vegetated site, the greater the number of bird species utilizing the site. Seventeen species of birds were categorized as residents. These resident bird species includes White-breasted Woodswallow, Pied Triller, Scaly-breasted Munia, Asian House-martin, Pacific Swallow, Long-tailed Shrike, Blue-throated Bee-eater, Olive-backed Sunbird, Sooty-headed Bulbul, Yellow-vented Bulbul, White-breasted Waterhen, Ashy Tailorbird, Yellow-bellied Prinia.